Cloning and expression of truncated CTCF - Ngan, Chot San (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
The CTCF gene maps on chromosome 16 at 16q21- q22.3. It encodes a transcriptional factor protein CTCF called zinc finger protein. CTCF has a number of fUnctions in the cell including controls of cell proliferation by having interactions with other proteins. There are several proteins associated with CTCF. Among them are proteins involved in transcriptional and cell proliferation control, RNA processing, signal transduction, nucleosome components and tumor suppressors. CTCF consists of N-terminal domain, zmc finger domain and C-terminal domain. Extensive research have been done to elucidate the important regions that might play important role in both DNA binding and protein-protein interactions. Previous studies has shown there was a region in the C-domain which has direct interaction with large subunit of RNA polymerase II and controlling various cellular process. In this study, a tnmcated CTCF from the C-terminal domain was produced by polymerase chain reaction (PCR). The amplified products was then subcloned into the intermediate cloning vector, pTOP02.1 and transformed into E. coli strain DH5 a. The insert was then cut with respective restriction enzyme to obtain the truncated region and further ligated into pETI6b expression vector for its expression in E. coli strain BL21 (DE3). Expressed protein was separated using SDS-PAGE followed by Western Blotting using a-Histag monoclonal antibody. The truncated CTCF protein was detected to migrate at the size ofapproximately 27kDa despite its theoretical size of 4kDa. This migration was expected and due to anomalous conformational changes during migration.